Enhanced sorption of aqueous cadmium (II) ions on phenylalanine modified activated carbon: ACRID 2017, June 20-21, Victoria Falls, Zimbabwe - Chikwanda, Prosper; Mugadza, Tawanda; Guyo, Upenyu (EAI, 2021)
Phenylalanine modified activated carbon sorbent (PAAC) was prepared and characterised using FTIR and XRD spectroscopic studies and scanning electron microscopy. The potential removal of Cd (II) ions from aqueous solutions using this sorbent was investigated through adsorptive experiments. The parameters evaluated in the batch studies included pH (2-9), PAAC dosage (0.1–1.2 g L−1), contact time (1–240 min), initial Cd (II) ion concentration (5-60 mg L-1) and temperature (10–50 oC). A dosage of 1.0 g L-1 of PAAC showed a near complete removal of 25 mg L-1 of the initial Cd (II) ion concentration from aqueous solution at pH 6 and a temperature of 25 oC. The equilibrium studies revealed that the experimental data fitted very well into the Langmuir isotherm model. Kinetic studies showed that the adsorption process followed pseudo-second-order and the thermodynamic parameters indicated that adsorption was spontaneous and endothermic in nature. Sorption results revealed that the PAAC is an efficient sorbent for the removal of Cd (II) ions from aqueous media.